Nanostructured Mn2O3/Pt/CNTs selective electrode for oxygen reduction reaction and methanol tolerance in mixed-reactant membraneless micro-DMFC. (20th February 2019) - Abrego-Martínez, J.C.; Wang, Youling; Moreno-Zuria, A.; Wei, Qiliiang; Cuevas-Muñiz, F.M.; Arriaga, L.G.; Sun, Shuhui; Mohamedi, Mohamed
Abstract: Mixed-reactant microfluidic direct methanol fuel cells (MR-μDMFCs) have the feature of achieving higher volumetric energy density in comparison with other DMFCs. The main challenge for the development of MR-μDMFC arises from the need for selective electrocatalysts, especially for the oxygen reduction reaction (ORR). In the present work, we report the two-step synthesis of a binder-free Pt and Mn2 O3 based catalyst by pulsed laser deposition. First an ultra-low loading Pt layer is deposited directly on carbon nanotubes and further coated with a porous Mn2 O3 layer. The resulting binary material exhibits practically identical electrocatalytic activity to that of Pt towards ORR in alkaline media. Interestingly, it shows no activity for the methanol oxidation reaction (MOR), in contrast with Pt. Furthermore, the Mn2 O3 /Pt cathode demonstrates to be tolerant to methanol concentration as high as 5 M. The results suggest that the superficial Mn2 O3 component discriminates between the molecular size of O2 and MeOH, allowing the former to reach the inner Pt layer and impeding the diffusion of the latter. The RRDE studies reveal that the ORR on both Pt/CNTs and Mn2 O3 /Pt/CNTs, is carried out through a 3.9 electron transfer. Lastly, the bilayer cathode is tested in a membraneless micro direct methanol fuel cell (ML-μDMFC) under mixed-reactant conditions, producing an OCV of 0.54 V and a maximum power density of 2.16 mW cm −2 .